Modelisation Des Changements D’occupation Des Terres En Region Soudanienne Au Nord-Ouest Du Benin - Agbanou Thierry; Paegelow Martin; Toko Imorou Ismaïla; Tente Brice (European Scientific Journal, ESJ, 2018)
In north-west Benin, land occupation is undergoing a significant dynamic due to intense human activities putting the ecosystem in precarious balance. The objective of this study is to quantify landscape dynamics and explore possible futures of land use using remote sensing, GIS and spatiotemporal modelling tools. Landsat socio-economic data and images (1987, 2000 and 2016) were used. A multi-date classification was used to quantify changes in land use. The Land Change Modeler (LCM) of the Terrset software was used to simulate and project land use to 2031. The results show that between 1987 and 2016, the landscape initially dominated by open wooded forests and savannahs (38,8 %) and wooded and shrubby savannahs (25,8 %) in 1987 was replaced in 2016 by land use categories including wooded and shrubby savannahs (40,5 %) and crop and fallow mosaics (50,6 %). The three scenarios Business-As-Usual (BAU), Rapid Economic Growth (CER) and Coordinated Environmental Sustainability (CED), extrapolating the current trends, show that by 2031 this landscape will be dominated by crop and fallow mosaics (+ 50 %). Wood resources occupy 26 % of the area of the sector in the CED scenario, 23 % in the BAU scenario and 19% in the CER scenario. The CED scenario gives hope that the restoration and preservation of plant resources is still possible if decision-makers become aware of it.